PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK - Hidayati, Nurul; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to find out the influence of Corporate Social Responsibility (CSR) and goodcorporate governance (independent commissioners, audit committees, audit quality) to the corporate taxavoidance. The research samples are 11 multinational companies manufacturing sector which are listed inIndonesia Stock Exchange (IDX) with 44 observations and these companies have been selected by usingpurposive sampling. The data analysis in this research has been carried out by using multiple regression analysisand Corporate Social Responsibility (CSR) independent variable which is proxy by the CSRDI, the proportion ofindependent commissioners, the number of audit committee, and audit quality (PAF size) to the tax avoidancewhich is proxy by current ETR.The result of the research shows that the CSR give positive influence to the taxavoidance. It means that when the CSR level is getting high (the company conducts a lot of disclosure of socialactivities item) the tax avoidance which is carried out by the company will be high as well. It is caused by someCSR items can reduce taxable income. Meanwhile, the independent commissioner, audit committee, and auditquality do not give any influence to the tax avoidance.Keywords: Corporate social responsibility, good corporate governance, tax avoidance